Investigating a lingual thyroid - Warnakulasuriya, K.A.A.S.; Herath, K.B. (International journal of oral and maxillofacial surgery, 1992)
During a 15-year-period, in a thyroid investigation centre in Sri Lanka comprising 16,593 cases, 8 lingual thyroids were seen. All patients were female. Radioisotope studies and scintiscanning performed during the investigations of these cases are presented. All subjects were euthyroid at presentation and the clinical courses of 5 cases during follow-up are discussed.